Neonatal Outcome of Macrosomia - Shah, Subhash Chandra; Guragain, Anusmriti; Pandey, Shreejana; Dhakal, Ajaya Kumar (Journal of Nepal Paediatric Society, 2020)
Introduction: Macrosomia is an emerging public health problem, both in the developed as well as in the developing countries. This study was aimed to examine the maternal and neonatal risk factors associated with macrosomia and compare adverse neonatal outcome between appropriate for gestational age (AGA) and macrosomia. Methods: Records of all live singleton AGA and macrosomic babies delivered at a tertiary care teaching hospital in Lalitpur, Nepal, between 14th April 2013 and 13th April 2014 were retrospectively reviewed. Results: Of the 769 deliveries, 684 neonates were eligible of which 93 were born macrosomic with an incidence of 12.1%. We observed the most significant neonatal outcome to be neonatal sepsis (14%; p = 0.005) compared to AGA babies (5.9%). Macrosomia was found to be associated with increasing maternal age and parity (p = 0.007) relative to mothers of AGA babies, most of whom underwent caesarean section (55.9%) whilst the same outcome was fewer for mothers of AGA babies (29.9%). A higher incidence of pregnancy induced hypertension (PIH) as maternal comorbidity (5.4%) was associated with macrosomia contrasted with mothers of AGA babies (4.4%). Conclusion: Macrosomic birth was found to be associated with relatively higher adverse neonatal outcome, warranting prolonged hospital admission than AGA births.